Al-Zarqali on instrumentation - Ushama, Imama Karim Manba; Kabbashi, Nassereldeen Ahmed (IIUM Press, 2011)
The objective of this chapter is to describe the innovation of Al-Zarqali. There were various astronomers during the Golden Age who flourished in the Muslim World, among them Abu Ishaq Ibrahim ibn Yahya Al-Zarqali. He is considered to be an instrument maker, mathematician and a foremost astronomer of his time